Value–rent–finance. (June 2020) - Purcell, Thomas F.; Loftus, Alex; March, Hug
In this paper, we develop a novel interpretation of the internal relationship between value, rent and finance, thereby enabling a new reading of the process of financialisation. As we argue, responding to the important question of how best to conceptualise the relationship between value and finance necessitates an understanding of the internal relations with a third moment, that of rent. We therefore develop a triadic understanding of these three interrelated moments. Crucially, we demonstrate that fictitious capital now actively pursues forms of rent, deepening the interrelationship between value, rent and finance. We conclude with a critical review of the literature on the financialisation of water, showing how the conceptual framework we develop sheds light upon the relations out of which water infrastructure has been financialised, as well as suggesting strategic entry points for its contestation.